Helicobacter pylori overcomes natural immunity in repeated infections. Issue 11 (23rd September 2016) - Stenström, Björn; Windsor, Helen M.; Fulurija, Alma; Benghezal, Mohammed; Kumarasinghe, M. Priyanthi; Kimura, Kazufumi; Tay, Chin Yen; Viiala, Charlie H.; Ee, Hooi C.; Lu, Wei; Schoep, Tobias D.; Webberley, K. Mary; et al.
Key Clinical Message: Repeated experimental reinfection of two subjects indicates that Helicobacter pylori infection does not promote an immune response protective against future reinfection. Our results highlight the importance of preventing reinfection after eradication, through public health initiatives, and possibly treatment of family members. They indicate difficulties for vaccine development, especially therapeutic vaccines. Abstract : Repeated experimental reinfection of two subjects indicates that Helicobacter pylori infection does not promote an immune response protective against future reinfection. Our results highlight the importance of preventing reinfection after eradication, through public health initiatives, and possibly treatment of family members. They indicate difficulties for vaccine development, especially therapeutic vaccines.